PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Nikmah, Nikmah; Apriyanti, Hera (JURNAL AKUNTANSI, 2016)
Many studies have been conducted to examine therelationship between intellectual capital andfinancial performance. However, those study stillshowed some inconsistencies. Therefore, this studyaimed to reexamine the effect of intellectual capitalon financial performance. The sample consists of 21manufacturing firms listed in Indonesia StockExchange during the observation period 2010-2013which chosen by purposive sampling method. Thetest results show that intellectual capital haspositive effect on financial performance whichmeasured by return on asset, market to book value ,market capital and earning per share, butintellectual capital has not effect on asset turnover.